2020
DOI: 10.3390/ma13184182
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Properties of Biocomposites Based on Polyethylene with a Natural Origin Filler

Abstract: The study investigates the effect of the content and size of wheat bran grains on selected properties of a lignocellulosic biocomposite on a polyethylene matrix. The biocomposite samples were made by injection method of low-density polyethylene with 5%, 10% and 15% by weight of wheat bran. Three bran fractions with grain sizes <0.4 mm, 0.4–0.6 mm and 0.6–0.8 mm were used. The properties of the mouldings (after primary shrinkage) were examined after their 2.5-year natural aging period. Processing properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Furthermore, absorption bands at 1650 and 1542 cm −1 , respectively, confirm the presence of protein C-N and N-H amide groups [ 86 ]. Moreover, absorption bands at 1151 cm −1 , 1076 cm −1 , 1017 cm −1 and 993 cm −1 result from the vibrations of the –C-O-C– and –C-O– groups found in polysaccharides [ 64 ]. Figure 12 also shows sample spectra of biocomposites obtained with the use of 10%, 30% and 50% of bran.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, absorption bands at 1650 and 1542 cm −1 , respectively, confirm the presence of protein C-N and N-H amide groups [ 86 ]. Moreover, absorption bands at 1151 cm −1 , 1076 cm −1 , 1017 cm −1 and 993 cm −1 result from the vibrations of the –C-O-C– and –C-O– groups found in polysaccharides [ 64 ]. Figure 12 also shows sample spectra of biocomposites obtained with the use of 10%, 30% and 50% of bran.…”
Section: Resultsmentioning
confidence: 99%
“…The WB conditioning process involved, successively, two-time grinding using a millstone, drying in a laboratory drier for 24 h at 80 °C, followed by sieving the dried WB with a moisture content of 3wt.% on a 5-sieve column shaker with the mesh size decreasing from 1 mm to 0.2 mm in order to obtain a fraction with a particle size below 0.2 mm. The particle size was selected as the smallest possible on the basis of previous studies, where an adverse effect of the particle size on the properties of the composition was found [ 42 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Characteristic absorption bands originating from the vibrations of C=O carbonyl groups (1714 cm −1 ) and ester bonds -C-O-C and -O-(C=O) at 1262 cm −1 , 1173 cm −1 , and 1044 cm −1 are observed on PBS spectrum. The structure of wheat bran is mainly composed of polysaccharides (including cellulose, hemicellulose, and lignin), phenolic and lipid compounds, and proteins, as confirmed by the FTIR spectrum [66,91]. The spectra of PBS composites with bran (Figure 9) show absorption bands originating from…”
Section: Chemical Structurementioning
confidence: 87%
“…Moreover, it was also shown that the filler particles act as a promoter of crystallization. This means that the arrangement of the crystalline phase occurs around the filler particles and the resulting volume loss exerts compressive stresses on them, which would further affect the shrinkage value [118,119]. At lower filler contents, the crystalline regions around the WB particles will be larger, whereas at 50% content, there will be more crystallization nuclei, but with smaller sizes, as the presence of filler will also limit the mobility of macromolecules [120,121].…”
Section: Transverse Shrinkagementioning
confidence: 99%